(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
In this article, we discussed the numerical solution of Brnoulli’s equation with fractional derivatives subject to initial value problems by applying 4th order Runge-Kutta, modified Runge-Kutta and Runge-Kutta Mersian methods. Here the solutions of some numerical examples have been obtained with the help of mathematica program as well as we determined the exact analytic solutions.